(untitled) (Bulletin of Innovative Research, 2026)
This article presents a psycholinguistic analysis of the short stories of Abdulla Qahhor, based on the example of the story “O‘jar”. The study focuses on the characters’ inner speech, expressive linguistic units, semantic associations, and psychological processes occurring in the reader’s mind. The cognitive and emotional impact of the literary text is analyzed from a psycholinguistic perspective.